The Role of Strigolactones and Their Potential Cross-talk under Hostile Ecological Conditions in Plants - Mishra, Sonal; Upadhyay, Swati; Shukla, Rakesh K. (Frontiers in Physiology, 2017)
The changing environment always questions the survival mechanism of life on earth. The plant being special in the sense of their sessile habit need to face many of these environmental fluctuations as they have a lesser escape option. To counter these adverse conditions, plants have developed efficient sensing, signaling and response mechanism. Among them the role of phytohormones in the management of hostile ecological situations is remarkable. The strigolactone, a newly emerged plant hormone has been identified with many functions such as growth stimulant of parasitic plants, plant architecture determinant, arbuscular mycorrhiza symbiosis promoter and also in many other developmental and environmental cues. Despite of their immense developmental potential, the strigolactone research in the last few years has also established their significance in adverse environmental condition. In the current review, its significance under drought, salinity, nutrient starvation, temperature and pathogenic assail has been discussed. This review also opens the research prospects of strigolactone to better manage the crop loss under hostile ecological conditions.